PENGARUH PELAKSANAAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH - DAIS SOLIHAT (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten, 2018)
Abstract Government regulation, states that regional finances should be managed on the basis of common principles of orderly, law-abiding, efficiency, economical, effective, transparent and accountable with due regard to the principles of justice, compliance and benefits to society. Therefore, to achieve effectiveness of regional expenditure, government must implementing the internal control. This research aims to analysis the influences of the implementation of internal control to the effectiveness of revenue and expenditure budget management of six local government in West Java Province. This research was conducted in Bandung municipal, Cimahi city, Tasikmalaya city, Tasikmalaya municipal, West Bandung municipal, and Bandung city. The data of research is collectible questionnaries with internal auditors as respondens. Spearman rank correlation is used for analysing the data. The result of this research in this research shows that the implementation of government internal control system is positively related to the effectiveness revenue and expenditure budget management, with the correlation coefficient is 0.816 on significant level is 0.01.